THE ANALYSIS OF MATHEMATICAL CREATIVE THINKING SKILLS AND SELF-EFFICACY OG HIGH STUDENTS BUILT THROUGH IMPLEMENTATION OF PROBLEM BASED LEARNING AND DISCOVERY LEARNING - Nani Ratnaningsih (STKIP Singkawang, 2018)
This research implements Problem Based Learning and Discovery Learning model  to analysis the increase of mathematical creative thinking skills, mistakes in the process of mathematical creative thinking, and self-efficacy of high school students  in Tasikmalaya.  The research  method  used is descriptive,  data collection  techniques  through  creative thinking ability tests and questionnaires mathematics self-efficacy. The instruments were previously assessed by experts in mathematics education. Based on the data analysis, it is concluded that the mathematical creative thinking abilities of students through Problem Based Learning is increasing compared to the mathematical creative thinking abilities of students through Discovery Learning. Mistakes students of mathematical creative thinking processes in Problem Based Learning, generally on flexibility and originality indicators. While at Discovery Learning, mistakes students of mathematical creative thinking processes is generally on sensitivity, flexibility and originality indicators. Flexibility is solving the problem with a variety of different ways, but the result is the same, and originality is to solve the problem in its own way does not use a standard formula. Sensitivity is the ability to detect problems. Self-efficacy of students in Problem Based Learning and Discovery Learning are both at high qualifications.